1979
DOI: 10.1128/aem.38.1.72-77.1979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Monensin and Lasalocid-Sodium on the Growth of Methanogenic and Rumen Saccharolytic Bacteria

Abstract: It is thought that monensin increases the efficiency of feed utilization by cattle by altering the rumen fermentation. We studied the effect of monensin and the related ionophore antibiotic lasalocid-sodium (Hoffman-LaRoche) on the growth of methanogenic and rumen saccharolytic bacteria in a complex medium containing rumen fluid. Ruminococcus albus, Ruminococcus flavefaciens, and Butyrivibrio fibrisolvens were inhibited by 2.5 ,ug of monensin or lasalocid per ml. Growth of Bacteroides succinogenes and Bacteroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
135
0
7

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(161 citation statements)
references
References 24 publications
19
135
0
7
Order By: Relevance
“…The selective toxicity of ionophores towards certain ruminal bacteria is a function of their ability to permeate the cell envelopes of some bacteria but not others (Chen & Wolin, 1979;Henderson et al, 1981;Bergen & Bates, 1984;Nagaraja & Taylor, 1987;Newbold et al, 1988;Russell & Strobel, 1989). Ionophores by definition translocate ions through biological membranes (Pressman, 1968), and this has been assumed to be their mode of action at the cellular level: ionophores that permeate the cell envelope will then disrupt transmembrane ionic gradients in accordance with their ion-translocating properties and cause toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selective toxicity of ionophores towards certain ruminal bacteria is a function of their ability to permeate the cell envelopes of some bacteria but not others (Chen & Wolin, 1979;Henderson et al, 1981;Bergen & Bates, 1984;Nagaraja & Taylor, 1987;Newbold et al, 1988;Russell & Strobel, 1989). Ionophores by definition translocate ions through biological membranes (Pressman, 1968), and this has been assumed to be their mode of action at the cellular level: ionophores that permeate the cell envelope will then disrupt transmembrane ionic gradients in accordance with their ion-translocating properties and cause toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Their nutritional effects are due largely to changes in the fermentation stoichiometry and the metabolism of dietary nitrogen by ruminal microorganisms (Bergen & Bates, 1984;Russell & Strobel, 1989;Duffield et al, 2012). These changes arise partly from the elimination of many Gram-positive bacteria (Chen & Wolin, 1979;Henderson et al, 1981;Nagaraja & Taylor, 1987;Newbold et al, 1988) and partly from adaptations which resistant Gram-negative bacteria undergo when grown in the presence of ionophores (Morehead & Dawson, 1992;Newbold et al, 1992;Callaway & Russell, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo experiments indicate that monensin decreases methane production, but methanogenic bacteria are not particularly sensitive to ionophores [29]. When mixed ruminal bacteria are incubated with H 2 and CO 2 , little decrease in methane is observed [29], but monensin can inhibit H 2 -producing ruminal bacteria that supply methanogens with H 2 [30]. Because bacteria that produce H 2 are more apt to produce acetate and butyrate than those that produce succinate and propionate, there is a change in ruminal fermentation acids (Fig.…”
Section: E¡ect Of Ionophores On Ruminal Bacteriamentioning
confidence: 99%
“…The ionophore, monensin, decreases the methane production of cattle, but it does not seem to have a primary e¡ect on methanogens [5]. When mixed ruminal bacteria were treated with monensin, methane production from hydrogen and carbon dioxide did not decrease [6], and later work showed that monensin was inhibiting carbohydrate fermenting bacteria that produced hydrogen [7]. Monensin decreased methane production from formate [8], but Hungate demonstrated that ruminal formate was converted to hydrogen and carbon dioxide before it was consumed by methanogens [9].…”
Section: Introductionmentioning
confidence: 99%